An Assessment of the Replication of Jesus' Social Ministry in the Nigerian Baptist Convention (2014)
Deep concern for the poor in the society was an integral part of Jesus' earthly ministry especially in the Gospel of Luke. This makes the social ministry an important part of a typical church, as manifested in the programmes of the Nigerian Baptist Convention (NBC). Many scholars have examined the theological basis of Jesus' care and concern for the poor, but adequate attention has not been given to the connection between Jesus' approaches and those of the NBC Social Ministry, devoted to alleviating poverty, following the example of Jesus. This study, therefore, evaluated the activities of Jesus among the poor with those of the Social Ministry Department of NBC (SMDNBC) with a view to establishing the biblical basis and the effectiveness of the activities of the Department. The study employed a historical-critical design. It adopted Gerald West's "Academy of the poor" framework. A total of 510 copies of a questionnaire were administered to members across 50 Baptist churches in Lagos (30), Ibadan (10) and Ogbomoso (10) selected on purposive and snowball bases. In-depth interviews were conducted with purposively selected five officials of the NBC at its headquarters in Ibadan, 30 pastors, 24 church officers and 33 church members. Church records were also consulted. Data were subjected to exegetical analysis, with reference to selected Lukan passages, and percentages. Jesus adopted five approaches in caring for the poor: identification, solidarity, education, advocacy and empowerment. Through identification, he properly recognised the authentic poor and differentiated them from other social classes (Luke 4:18,7:20); and through solidarity, he united with them in genuine friendship (Luke 2:1-7, 2:8-20, 9:58). Through education, he instructed them on their rights, status and how they could find peace (Luke 12:33,18:18-25); and through advocacy, he spoke against the oppression of the poor. (Luke 16:19-31, 21:1-4,3:1-14) Through empowerment, he engaged in spiritual, mental and economic uplift of the poor (Luke 16:19-31,6:20, 19:1-10). Contrariwise, only two of the approaches were relatively adopted by the SMDNBC: education in which it provided both formal and informal education though at a relatively high fee, and empowerment in which it provided means of earning a living for widows and prisoners. Little or no attempt was made to identify, establish solidarity and achieve advocacy as Jesus did. The implication of this deficiency was evident in the responses of the respondents in which 50.4% of the respondents were not aware of the SMDNBC, while 70.8% opined that lack of proper care for the poor had resulted in 30.0% loss of membership. Only 5.4% of the respondents had received assistance from SMDNBC. The Social Ministry Department of the Nigerian Baptist Convention adopted only two out of the five approaches used by Jesus Christ in reaching the poor which revealed an inconsistency with the biblical standard. This made the ministry less effective and led to membership shrink. It is, therefore, recommended that the NBC needs to completely adopt the five approaches of Jesus in Luke in order to enhance the effectiveness of its social ministry